The intrapersonal normative twin earth argument - Hambly, Jesse (Synthese, 2024)
In this paper I develop an argument against applying a causal theory of mental content to normative concepts. This argument—which I call the Intrapersonal Normative Twin Earth Argument—is inspired by Terry Horgan and Mark Timmons’ Moral Twin Earth Argument. The focus of Horgan and Timmons’ argument is showing that causal theories of mental content conflict with plausible claims about interpersonal normative disagreement. The Intrapersonal Normative Twin Earth Argument, by contrast, is focused on showing that such theories struggle to vindicate plausible claims concerning whether two of an agent’s token normative thoughts have the same or distinct content.